Meningioangiomatosis: Multimodal Analysis and Insights From a Systematic Review. (9th February 2021) - Roux, Alexandre; Zanello, Marc; Mancusi, Rossella Letizia; Still, Megan E.H.; Nascimento, Fábio A.; Tauziede-Espariat, Arnault; Huberfeld, Gilles; Zah-Bi, Gilles; Dezamis, Edouard; Meder, Jean-François; Bourgeois, Marie; Parraga, Eduardo; et al.
Abstract : Background: Meningioangiomatosis is a poorly studied, rare, benign, and epileptogenic brain lesion. Objective: To demonstrate that surgical resection and a short-time interval to surgery improves epileptic seizure control, we performed a systematic review and meta-analysis of meningioangiomatosis cases. Methods: Using PRISMA-IPD guidelines, the authors performed a systematic review and meta-analysis of histopathologically-proven meningioangiomatosis cases. Literature search in French and English languages (PubMed, Embase, the Cochrane Library, and the Science Citation Index) including all studies (January 1981 to June 2020) dealing with histopathologically-proven meningioangiomatosis, without age restriction. We assessed clinical, imaging, histomolecular, management, and outcome findings of patients with meningioangiomatosis. Results: Two-hundred and seven cases of meningioangiomatosis from 78 studies were included. Most meningioangiomatosis was sporadic, preferentially concerned male patients, younger than 20 years old, and allowed a functionally independent status. Epileptic seizure was the main symptom, with 81.4% of patients having uncontrolled seizures at the time of surgery. Meningioangiomatosis mainly had frontal (32.3%) or temporal (30.7%) locations. Imaging presentation was heterogeneous, and the diagnosis was often missed preoperatively. The histopathologic pattern was similar whatever the clinical presentation, and immunohistochemistry had limited diagnostic value. On molecular analysis, allelic loss at 22q12 was more frequent in samples of meningioangiomatosis-associated meningioma (37.5%) than in isolated meningioangiomatosis (23.1%). Time interval from diagnosis to surgery ( p = 0.011) and lack of surgical resection of the meningioangiomatosis ( p = 0.009) were independent predictors of postoperative seizure control. Conclusions: Owing to low scientific evidence, a multicentric prospective study should help refining the management of meningioangiomatosis.